2019
DOI: 10.1155/2019/9035837
|View full text |Cite
|
Sign up to set email alerts
|

Lamellar Macular Holes: The Role of Microperimetry in Functional Assessment

Abstract: Introduction. The aim of our observational cross-sectional study was to evaluate the association between visual function and anatomical characteristics of LMH, considering in particular different subtypes of LMH and their features. Materials and Methods. This observational clinical study has been conducted in the Ophthalmology Clinic, ASST-Sette Laghi, University of Insubria of Varese-Como, Italy. Included patients underwent a complete ophthalmological examination, as well as MP1 microperimetry evaluation and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 21 publications
0
2
0
Order By: Relevance
“…Both kinds of membrane show some common immunohistochemical profiles, such as CD45, CD64, and glial fibrillary acidic protein: these biomarkers are typically expressed by hyalocytes and glial cells, underlying the role of these cells in the pathogenesis of this macular disease [ 66 ]. The differences between these two clinical features gain more and more evidence if we consider their progression and impact on visual function, that is, more severe in LMH with epiretinal proliferation, probably due to deeper alterations in outer retinal layers [ 68 ], in particular to the ELM [ 69 ].…”
Section: Main Textmentioning
confidence: 99%
See 1 more Smart Citation
“…Both kinds of membrane show some common immunohistochemical profiles, such as CD45, CD64, and glial fibrillary acidic protein: these biomarkers are typically expressed by hyalocytes and glial cells, underlying the role of these cells in the pathogenesis of this macular disease [ 66 ]. The differences between these two clinical features gain more and more evidence if we consider their progression and impact on visual function, that is, more severe in LMH with epiretinal proliferation, probably due to deeper alterations in outer retinal layers [ 68 ], in particular to the ELM [ 69 ].…”
Section: Main Textmentioning
confidence: 99%
“…As presented before, OCT plays an important role in the evaluation of LMH structure and morphology. Recent studies have shown interesting results using short-wavelength fundus autofluorescence (SW-FAF) [ 70 ] and microperimetry to assess retinal sensitivity (RS) [ 68 , 70 ]. Larger LMHs show hyper-FAF area combined to lower preoperative RS.…”
Section: Main Textmentioning
confidence: 99%